Mapping Freshwater Subaqueous Soil Resources: Examples from Southern New England. Issue 2 (22nd February 2018) - Bakken, Jonathan; Stolt, Mark H.
Abstract : Core Ideas: Soil series were developed for Humaquepts, Frasiwassists, and Psammentic and Aeric Frasiwassents. GPR technology provided accurate analysis of water depth, substrate type, and organic thickness. We identified five soil‐landscape units: lakebed, shoals, shoreline, coves, and deepwater. Subaqueous soils are those that occur under permanently flooded or ponded environments. Few studies have investigated freshwater subaqueous soil systems. In this study, we used traditional and modified soil survey techniques to investigate subaqueous soils in three created (impoundments) and three natural freshwater lakes in southern New England. The objectives were to test the effectiveness of bathymetric maps and ground‐penetrating radar (GPR) for establishing soil–landscape relationships in freshwater subaqueous systems, compare soil types between natural and impounded systems, and investigate the genesis of these soils. Bathymetric data were collected with a fathometer to create topographic maps of the lake bottoms to delineate subaqueous landscapes. Ground penetrating radar transects were run across landscape units to test the effectiveness of this technology to identify soil properties that could be used to separate mapping units. The primary landscape units identified included lakeshores, coves, lakebeds, and shoals. Lakebed and lakeshore units comprised 71 to 90% of the landscape regardless of whether the water bodies were natural or impounded. Ground penetrating radar was effective at identifying the presence of stones and boulders at the soil surface, stratified mineral layers, and the thickness of organic soil materials. Eighty‐one pedons were characterized and classified as Frasiwassists (34), Frasiwassents (32), and Humaquepts (18). All three great groups were identified in both natural and impounded systems with Frasiwassists the dominant soil type in all of the impounded sites. The primary soil processes included melanization resulting in umbric epipedons and organic matter accumulation resulting in histic epipedons in impounded sites with dense invasive vegetation. Frassiwassists were likely developed prior to submergence in both the natural and impounded systems.